The Extended Oxidative and Sensory Stability of Traditional Dairy-Based Oil with Steam-Distilled Essential Oils Extracted from the Bioactive-Rich Leaves of Ziziphora tenuior, Ferulago angulata, and Bunium persicum - Mehrdad Mohammadi; Nasim Khorshidian; Seyed Mohammad Taghi Gharibzahedi (Journal of Food Quality)
The oxidation rate and overall sensory acceptability of Iranian animal oil (IAO) during storage were evaluated after adding the bioactive essential oils extracted from medicinal herbs of Ziziphora tenuior, Ferulago angulata, and Bunium persicum. Results showed that the most dominant chemical constituents in Z. tenuior, F. angulata, and B. persicum essential oils were pulegone (12.77%), ferulagon (14.97%), and (+)-trans-carveol (57.70%), respectively. IAO contained more saturated fatty acids (67.43%, mainly palmitic and myristic acids) than unsaturated (32.27%, mostly oleic acid) ones. B. persicum essential oil compared to the other two oils significantly had more total flavonoid (1.08 mg quercetin equivalent/g), phenolic (123.2 mg GAE/g), carotenoid (591.31 mg/kg), and chlorophyll (24.32 mg/kg) contents. A significant dose-dependent increase in the overall sensory acceptability of IAO was found by increasing the concentration of B. persicum essential oil. Similar to tertiary butyl hydroquinone, the oil blend of IAO+10% B. persicum essential oil obtained the maximum overall sensory acceptability scores during 28 d cold storage due to the remarkable in vitro DPPH inhibition (83.45%) and ferric-reducing power (0.754 at Å700nm). A much slower formation rate in primary and secondary oxidation compounds in IAO rich in B. persicum essential oil during the storage was associated with the overall sensory acceptability data (p<0.01, r = 0.951). Thus, this bioactive additive as a bio-preservative may well stabilize crude oils and emulsions.